2000
DOI: 10.1128/mcb.20.13.4826-4837.2000
|View full text |Cite
|
Sign up to set email alerts
|

Specific Protein-Protein Interaction between Basic Helix-Loop-Helix Transcription Factors and Homeoproteins of the Pitx Family

Abstract: Homeoproteins and basic helix-loop-helix (bHLH) transcription factors are known for their critical role in development and cellular differentiation. The pituitary pro-opiomelanocortin (POMC) gene is a target for factors of both families. Indeed, pituitary-specific transcription of POMC depends on the action of the homeodomain-containing transcription factor Pitx1 and of bHLH heterodimers containing NeuroD1. We now show lineage-restricted expression of NeuroD1 in pituitary corticotroph cells and a direct physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 70 publications
(116 reference statements)
4
122
1
3
Order By: Relevance
“…Nonetheless, transcriptional synergism due to physical interaction of homeodomains with other transcription factors is well documented. For example, Pitx HD interacts with basic helix-loop-helix proteins on the proopiomelanocortin promoter, whereas Pdx1 HD interacts with Pan1 on the rat insulin promoter (8,73).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, transcriptional synergism due to physical interaction of homeodomains with other transcription factors is well documented. For example, Pitx HD interacts with basic helix-loop-helix proteins on the proopiomelanocortin promoter, whereas Pdx1 HD interacts with Pan1 on the rat insulin promoter (8,73).…”
Section: Discussionmentioning
confidence: 99%
“…1, A (lanes 2, and 4) and B (lane 6)) was ascribed to the Ebox neuro and to basic helix-loop-helix factors (25). Prior work indicated that the NurRE and the cognate Nur factors contribute to basal activity as well as to POMC promoter responsiveness to the hypothalamic hormone CRH (5, 7), whereas the Ebox neuro contributes to basal activity (26,27).…”
Section: Rbmentioning
confidence: 99%
“…There is an extensive precedent for functional cooperativity between bHLH and homeodomain proteins in regulating developmental processes: for example, during neurogenesis and retinogenesis bHLH proteins drive neuronal fate and differentiation while homeodomain protein activities specify particular cellular subtypes. 9,[41][42][43][44][45] This can involve direct transcriptional coordination between homeodomain and bHLH proteins bound to adjacent sites in target gene enhancers. 46 Therefore, it will be interesting to determine whether Geminin's interactions with both homeodomain proteins and SWI/SNF provide a dual negative regulatory mechanism at target genes coordinately regulated by bHLH, homeodomain, and SWI/SNF protein complexes.…”
Section: A B C Dmentioning
confidence: 99%